NILAI-NILAI PENDIDIKAN NOVEL SANG PEMIMPI KARYA ANDREA HIRATA - Fitriati, Siti (JURNAL PESONA, 2015)
AbstractThis study aims to determine the message of education values in Sang Pemimpi novel by Andrea Hirata. The message of education values as the indicators in this study are moral value, beauty value, religious value and the truth value. The data of this research is from Sang Pemimpi novel by Andrea Hirata. Method of this study uses qualitative descriptive, it means that decomposes the data in the words form; it is not in the numbers form. The novel that used in this study was analyzed and interpreted according to the novel condition based on the theory, then described according to the objective of the study. The result and discussion shows Sang Pemimpi novel by Andrea Hirata can be concluded that the novel has educational values including moral values such as helpfulness attitude, courage and commitment, cooperation, caring and empathy, humor, responsibility, beauty value, religious value and truth value.Â Key Words: Literature; Novel; Education Value.Â